Isorhamnetin decreased the expression of HMG-CoA reductase and increased LDL receptors in HepG2 cells - Randa El-Rayyes, Manal M. Abbas,, Razan Obeidat, Manal A. Abbas, (Journal of Applied Pharmaceutical Science, 2023)
Isorhamnetin is a flavonoid present in many plants. In a previous in vivo study, isorhamnetin lowered the serum cholesterol of rats fed a high-cholesterol diet. However, its mechanism of action was not investigated. In the present work, the mechanism of its hypocholesterolemic effect was studied. The expression of 3-hydroxy-3-methylglutaryl- CoA reductase (HMG-CoA reductase) and low-density lipoprotein receptor (LDLR) genes and proteins was studied in HepG2 liver cancer cell line by polymerase chain reaction, western blot, and indirect enzyme-linked immunosorbent assay as well as its antioxidant activity. isorhamnetin had an IC50 of 100, 53, and 40 μM at 24, 48, and 72 hours, respectively, in HepG2 cells. Isorhamnetin downregulated HMG-CoA reductase gene expression significantly. Also, all tested doses of isorhamnetin downregulated LDLR expression and produced no change in membranous LDLR protein expression. In cell lysate, LDLR was increased by all studied concentrations of isorhamnetin. Isorhamnetin (100 μM) decreased intracellular HMG-CoA reductase compared to vehicle-treated control. Furthermore, isorhamnetin increased superoxide dismutase activity and reduced H2O2 level, due to catalase activity. Isorhamnetin reduced HMG-CoA reductase gene expression and increased total LDLR and exerted pronounced antioxidant action.